Star cluster detection with WFC/ACS in M 33, 33 new clusters and 51 candidates - Bedin, L.R. (2005)
In this work we present the detection of 33 star clusters and 51 candidates in one field of the near by galaxy M 33. This study is based on WFC/ACS images available from the HST archive. Thanks to the high resolving power, we were able to confirm that two candidates previously indicated by Christian & Schommer (1982, ApJS, 49, 405) are indeed star clusters. We list the main properties for the star clusters (and candidates), along with some peculiar objects, such as background galaxies and possible HII regions. © ESO 2005.